Histomorphometric evaluation of the effects of local application of red cloveroil (trifolium pratense) on bone healing in rats - AL-Ghaban , Nada M; Jasem , Ghazwan H (Journal of Baghdad College of Dentistry, 2020)
Background: Red clover oil (Trifolium pratense) has isoflavones bunches which have estrogen-like exercises and may establish an option in contrast to hormone substitution treatment. The present study investigated the impact of Red clover oil on bone healing in rats by histomorphometric study. Materials and Methods: Intra bony defect was performed in right femur of thirty six healthy male albino rats. Then these rats were randomly divided into three groups (12 rats each): one control and 2 experimental groups. For control, the bony defect was left for normal healing; for the experimental (S) group, the defect was treated with hemostatic absorbable gelatin sponge; and for experimental (RS) group, the bony defect was treated with 0.2 ml red clover oil and covered by haemostatic absorbable gelatin sponge. Six rats from each group were sacrificed at 2 and 4 weeks intervals. Histomorphometric analysis was performed on H&E bone section of all the studied groups which includes counting of bone cells (osteoblasts, osteocytes and osteoclasts), trabecular number, trabecular area and bone marrow space area. Results: Histomorphometric results of bone cells revealed that the combination group stimulated larger numbers of osteoblasts and osteocytes than in sponge and control group. Number of new bone trabeculae, trabecular area and bone marrow space area showed higher mean values in combination groups than others. Highly significant differences between groups were observed in all histomorphometric parameters throughout all durations. Conclusion: Red clover oil stimulated larger numbers of osteoblasts and osteoclasts, indicating increased bone remodeling especially at 2 weeks interval as compared with sponge and control groups. Key words: Bone defect, Red clover, Rats.